47 Doctors Administrators a novel addition to the non-medical workforce. (16th November 2020) - Dixon, Angela; Short, Jennifer; Bickerstaff, Andrew; Scott, Sharon; MacDougall, Claire; Mackie, Helen
Abstract : Introduction: We describe a project to introduce a novel non- medical role to support Medical staff, the 'Doctors administrator', and to improve the quality and timeliness of the final discharge summary letter (DSL) being sent to primary care teams. A bespoke a training program was developed which included, ward clerk duties, typing, medical terminology and coding. DAs were trained to produce DSLs, which consultants then verified or amended electronically, before forwarding to the GP. Pilot phase: 6 months 3WTE DAs produced 260 DSL each month. Two consultants acted as supervisors. This relationship was key to building confidence and capability and to ensure high quality of the letters. A very early quality indicator was the percentage of letters typed within 3 Days. Letter typed within 3 days% by consultant PRE – DA POST –DA Consultant A 55.4% 67.6% Consultant B 8.6% 71.2% Full implementation: DA's now act on behalf of 13+ consultants producing over 550 DSL monthly. Assuming each DSL takes around 15 minutes, we estimate DA's save around 120 hours consultant time monthly. A standardised format ensures key information is not omitted facilitating more accurate coding and data collection. Consultants and DAs are highly satisfied. Consultants felt there was less burden of basic admin tasks. 'the time I now spend on admin has significantly reduced and is much more structured' Feedback from GP's was positive and improved timeliness of communication had been observed. Safety: There have been 3 Clinical incidents recorded during the whole period, both related to onward results/referral management. All incidents were investigated and safeguarding actions put in place e.g. copying of onward referrals to specialist's teams. Conclusions: Doctors administrators are safe and effective and reduce clinical workload. Whilst we have utilised this resource for DSL for we believe this role could be expanded and developed in other clinical contexts.